2004
DOI: 10.1046/j.1365-2958.2003.03844.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual RD1‐region genes are required for export of ESAT‐6/CFP‐10 and for virulence of Mycobacterium tuberculosis

Abstract: SummaryThe RD1 genomic region is present in virulent strains of Mycobacterium tuberculosis (MTB), missing from the vaccine strain M. bovis BCG, and its importance to virulence has been established experimentally. Based on in silico analysis, it has been suggested that RD1 may encode a novel secretion system, but the mechanism by which this region affects virulence is unknown. Here we examined mutants disrupted in five individual RD1 genes. Both in vitro and in vivo , each mutant displayed an attenuated phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
470
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(495 citation statements)
references
References 54 publications
15
470
0
5
Order By: Relevance
“…Moreover, D-Mtb-infected macrophages maintain their capacity to digest proteins in acidic compartments differently from R-Mtb-infected macrophages. These results indicate that D-Mtb is not endowed with the ability to arrest the phagosome maturation that characterizes R-Mtb, showing in this respect analogy with HK M. tuberculosis, BCG, and other M. tuberculosis mutant strains (41).…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, D-Mtb-infected macrophages maintain their capacity to digest proteins in acidic compartments differently from R-Mtb-infected macrophages. These results indicate that D-Mtb is not endowed with the ability to arrest the phagosome maturation that characterizes R-Mtb, showing in this respect analogy with HK M. tuberculosis, BCG, and other M. tuberculosis mutant strains (41).…”
Section: Discussionmentioning
confidence: 77%
“…Immune response to MTB infection is primarily mediated by T cells (Lockhart et al 2006). In previous research of human pulmonary TB, T cells responding to ESAT-6 are observed in approximately half of the patients (Guinn et al 2004;Reiley et al 2008). ESAT-6, a vital immune-dominant antigen encoded by region of difference-1 (RD1) and RD2, has been reported to have the potential for human MTB diagnosis (Sang and Zhang 2012;Li et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Sec substrates are translocated across the cytoplasmic membrane in an unfolded state, whereas Tat substrates are translocated in a folded conformation. M. tuberculosis also has at least two specialized protein export pathways: the SecA2-dependent system and the ESX-1 (ESAT-6) system (Braunstein et al, 2003;Guinn et al, 2004;Hsu et al, 2003;Pym et al, 2003;Stanley et al, 2003). Interestingly, both pathways appear capable of secreting specific subsets of proteins that lack conventional Sec or Tat signal sequences.…”
Section: Introductionmentioning
confidence: 99%